Targeting patient recovery priorities in degenerative cervical myelopathy: design and rationale for the RECEDE-Myelopathy trial—study protocol. Issue 3 (7th March 2023) - Davies, Benjamin; Mowforth, Oliver D; Yordanov, Stefan; Alvarez-Berdugo, Daniel; Bond, Simon; Nodale, Marianna; Kareclas, Paula; Whitehead, Lynne; Bishop, Jon; Chandran, Siddharthan; Lamb, Sarah; Bacon, Mark; et al.
Abstract : Introduction: Degenerative cervical myelopathy (DCM) is a common and disabling condition of symptomatic cervical spinal cord compression secondary to degenerative changes in spinal structures leading to a mechanical stress injury of the spinal cord. RECEDE-Myelopathy aims to test the disease-modulating activity of the phosphodiesterase 3/phosphodiesterase 4 inhibitor Ibudilast as an adjuvant to surgical decompression in DCM. Methods and analysis: RECEDE-Myelopathy is a multicentre, double-blind, randomised, placebo-controlled trial. Participants will be randomised to receive either 60–100 mg Ibudilast or placebo starting within 10 weeks prior to surgery and continuing for 24 weeks after surgery for a maximum of 34 weeks. Adults with DCM, who have a modified Japanese Orthopaedic Association (mJOA) score 8–14 inclusive and are scheduled for their first decompressive surgery are eligible for inclusion. The coprimary endpoints are pain measured on a visual analogue scale and physical function measured by the mJOA score at 6 months after surgery. Clinical assessments will be undertaken preoperatively, postoperatively and 3, 6 and 12 months after surgery. We hypothesise that adjuvant therapy with Ibudilast leads to a meaningful and additional improvement in either pain or function, as compared with standard routine care. Study design: Clinical trial protocol V.2.2 October 2020. Ethics and dissemination: Ethical approval has been obtained from HRA—Wales.The results will be presented at an international and national scientific conferences and in a peer-reviewed journals. Trial registration number: ISRCTN Number: ISRCTN16682024 .